Insecticidal properties of Piper nigrum fruits extracts and essential oils against Spodoptera litura. - Fan, Siew Loh; Muhamad Awang, Rita; Omar, Dzolkhifli; Rahmani, Mawardi (Friends Science Publishers, 2011)
Chemical analysis by GC and GC-MS revealed presence of 39 compounds in the essential oil fraction of Piper nigrum fresh fruits. Limonene was the major compound present with 35.06% of total oil followed by beta-pinene (12.95%) and linalool (9.55%). Insecticidal properties of Piper nigrum fruit extracts and essential oils were investigated against tobacco army worm, Spodoptera litura using topical application bioassay on uniform weighted second instar larvae in the laboratory. The hexane extract was most effective in killing the larvae and showed the highest toxicity at 48 h after treatment. Toxicity of extracts decreased in the order of hexane (LD50: 1.8 mg/g) > acetone (LD50: 18.8 mg/g) > chloroform (LD50: NA, the toxicity was very low) > essential oil (no mortality). Insect development and growth index observations showed that the hexane extract had antifeedant properties resulting in severe growth inhibition of Spodoptera litura.